Safety, adherence and discontinuation in varenicline solution nasal spray clinical trials for dry eye disease - Alan G Kabat; Mandy Hemphill; Karan Somaiya; Laura H Hendrix; Andrea A Gibson (Becaris Publishing Limited, 2023)
Aim: Herein, we report safety outcomes for varenicline solution nasal spray (VNS) within the context of clinical trial discontinuation, contrasting those with discontinuation outcomes from topical cyclosporine and lifitegrast clinical trials. Materials & methods: 1061 subjects were randomized across three clinical trials to receive either VNS 0.06 mg, VNS 0.03 mg, VNS 0.006 mg or vehicle control. Subjects who discontinued from treatment were noted and assigned to their appropriate categories. Results: Despite treatment emergent adverse events, 93.5% of subjects receiving VNS completed the treatment period. By comparison, only 80% of subjects in the integrated clinical trials for cyclosporine ophthalmic emulsion and 91% of subjects in the integrated trials for lifitegrast ophthalmic solution completed the full treatment period, respectively. Conclusion: In clinical trials, VNS demonstrated improvements in dry eye disease signs and symptoms, was well-tolerated, and had an overall completion rate >93%. Conventional dry eye treatments (e.g., cyclosporine and lifitegrast) noted considerably higher discontinuation rates in their clinical trials.